Isolation and Characterization of Soil Myxobacteria from Nepal - Rana, Nabin; Khadka, Saraswoti; Marasini, Bishnu Prasad; Joshi, Bishnu; Poudel, Pramod; Poudel, Pramod; Khanal, Santosh; Parajuli, Niranjan (Journal of Institute of Science and Technology, 2019)
Realizing myxobacteria as a potential source of antimicrobial metabolites, we pursued research to isolate myxobacteria showing antimicrobial properties. We have successfully isolated three strains (NR-1, NR-2, NR-3) using the Escherichia coli baiting technique. These isolates showed typical myxobacterial growth characteristics. Phylogenetic analysis showed that all the strains (NR-1, NR-2, NR-3) belong to the family Archangiaceae, suborder Cystobacterineae, and order Myxococcales. Furthermore, 16S rRNA gene sequence similarity searched through BLAST revealed that strain NR-1 showed the closest similarity (91.8 %) to the type strain Vitiosangium cumulatum (NR-156939), NR-2 showed (98.8 %) to the type of Cystobacter badius (NR-043940), and NR-3 showed the closest similarity (83.5 %) to the type of strain Cystobacter fuscus (KP-306730). All isolates showed better growth in 0.5-1 % NaCl and pH around 7.0, whereas no growth was observed at pH 9.0 and below 5.0. All strains showed better growth at 32° C and hydrolyzed starch, whereas casein was efficiently hydrolyzed by NR-1 and NR-2. Besides, preliminary antimicrobial tests from crude extracts showed activities against Gram-positive, Gram-negative bacteria, and fungi. Our findings suggest that the arcane soil habitats of Nepal harbor myxobacteria with the capability to produce diverse antimicrobial activities that may be explored to overcome the rapidly rising global concern about antibiotic resistance.